Islam and the west: from clash to dialogue - Bakour, Bachar (The Centre for Civilisational Dialogue, University of Malaya, 2018)
No doubt that the present fluctuating relation between Islam and the West is, and has always been, coloured by earlier encounters, (the spread of Islam, the Crusades, the Reconquista of Spain, the Inquisitions, to name a few). This article readdresses Islam-West relation by examining the fundamental underpinnings of the clash theory as delineated by Bernard Lewis in "The Roots of Muslim Rage" and Samuel Huntington in "The Clash of Civilizations." Though Lewis laid the foundation of civilizational conflict, it was Huntington who later fashioned and set the parameters of this conflict. The article also attempts to forge the idea of mutual understanding and dialogue by way of building bridges of scholarship, knowledge, respect and cooperation between people within this global village. To achieve this goal, the article highlights seven principles of the Islamic perspective of dialogue, drawing practical precedence from Islamic history, particularly from the Prophetic as well as the rightly-guided Caliphs' era.